Distribution of Complement Component 4 (C4) Isotype -A Null Phenotype (C4AQ0) in Normal Healthy North Indian Subjects - Mansoori, Riyaz Alam; Gandhi, Monika (Asian Journal of Biological and Life Sciences, 2012)
Complement system is a part of innate immunity and plays a very active role in protecting against various infections and disorders. C4 component is an important part of complement. The great genetic diversity and quantitative and qualitative variations of C4 have been revealed. Deficiencies of this protein have been found to be associated with various autoimmune and infectious diseases. Two isotypes have been found to exist for C4 namely C4A and C4B. The partial deficiency of C4A (C4AQ0) or C4B (C4BQ0) has been found to be associated with various disorders. A 2bp insertion in exon 29 of C4 gene has been found to be the reason for lowering of C4 expression. The distribution of C4AQ0 null phenotype has been studied in various populations. However such a study has not been done in Indian population, particularly the north Indian population. In this study we, for the first time have tried to find out the frequency distribution of C4AQ0 (C4A null phenotype) in north Indian population. Sixty normal healthy individuals from north India with their informed consent were recruited for this study, with an aim of determining the genetic distribution of C4AQ0 (null phenotype). Sequence specific PCR was used for this study. Results revealed that 3.3% of normal individuals possess C4AQ0 and that the distribution of C4AQ0 in Indian population resembles that of .European andAmerican population.